THE USE OF TEAM GAME TOURNAMENT (TGT) STRATEGY IN TEACHING VOCABULARY - Syamsinar Syamsinar; Syarifuddin Dollah; Munir Munir (State University of Makassar, 2026)
The purpose of this study was to ascertain whether or not students' vocabulary is considerably enhanced by the Team Game Tournament (TGT) technique. The pre-experimental design with a single group pre-test and post-test was used by the researcher. Fifteen eleventh-grade students from SMK Putra Bangsa Bulukumba participated in this study. They were selected using cluster sampling techniques. A vocabulary exam served as the research tool. Using the significance test method, the pre-test and post-test results utilizing the Team Game Tournament (TGT) strategy to enhance students' vocabulary revealed that the t-test value was less than P (0.000 < 0.05). Consequently, the accepted one was the alternative hypothesis (H1), and the rejected one was the null hypothesis (H0). After analyzing the N-Gain value, the result indicated that using the TGT strategy was classified as good. In conclusion, using the TGT strategy effectively enhances students' vocabulary, particularly in understanding meaning, spelling, pronunciation, word classes, and word use. Keywords: Team Game Tournament Strategy, Vocabulary Learning.